Study the incidence of bacterial and fungal contaminants in imported chicken femurs - Al-Hissen, Sanaria F. (The Iraqi Journal of Veterinary Medicine, 2005)
Incidence of bacterial and fungal contaminants in imported chicken femurs wasdetermined and compared with standard microbiological limits. A total of (12) Kgof imported chicken femurs were randomly collected at two batches from (6) areasin Baghdad city. Total aerobic bacterial count, coli form count and Staphylococcusaureus count were used as an indicator for bacterial contamination, in addition toyeast and mould count as an indicator for fungal contamination.Data revealed that skins of imported chicken femurs produced high level ofcontamination, in which most of the bacterial counts were near the maximumstandard limit as well as contamination with fungi, whereas the level ofcontamination in the meat of these femurs were low in comparison with standardlimits.